Pemberdayaan Masyarakat Desa Janti Melalui Pelatihan Pengelolaan Sampah Organik Berbasis Biopori Dengan Pendekatan CBPR - Haniyah, Haniyah; Sri Wahyuni Hamzah, Yayu; Puji Lestari, Utami; Muhammad Ramadhani, Fadhil; Bayustira, M. Saul; Nabila Ahmad, Atina (Journal of Research Applications in Community Service, 2025)
Household organic waste remains a major environmental challenge in Desa Janti, Kabupaten Sidoarjo. The community demonstrates high awareness of environmental issues, yet access to practical technical training is still limited. This community service program aims to enhance residents’ capacity in managing organic waste through training and hands-on practice in constructing biopore infiltration holes, using a Community-Based Participatory Research (CBPR) approach. The program involved 15 participants and was implemented in three main stages: socialization, practical training, and continuous mentoring. Participants’ success was assessed through direct observation, satisfaction questionnaires, and in-depth interviews. The results showed that 13 participants (85%) successfully applied biopore techniques in their homes, and environmental cadres were formed to support and guide other residents. Beyond the direct impact on organic waste reduction, the program fostered collective awareness in maintaining environmental cleanliness. Scientifically, this activity demonstrates the effectiveness of CBPR in empowering communities for sustainable household waste management and provides a replicable model for other regions.